The Art of Getting Over: Exploring gender equality in the graffiti subculture - Davies, Susie (UXUC - User Experience and Urban Creativity, 2020)
Throughout graffiti’s history, women have been ignored, sexualised and undermined. But despite the subculture’s history of gender imbalance, female graffiti writers are on the increase. This paper examines the reasons why more women are practising graffiti and evaluates the extent to which equality has been achieved. A focus on the North East of England reveals a persisting lack of female graffiti writers. While graffiti in larger cities such as London have somewhat diversified, in smaller and more isolated scenes gender perhaps remains imbalanced and should prompt further research.